Ascaris lumbricoides and ticks associated with sensitization to galactose α1,3-galactose and elicitation of the alpha-gal syndrome - Murangi, Tatenda; Prakash, Prema; Moreira, Bernardo Pereira; Basera, Wisdom; Botha, Maresa; Cunningham, Stephen; Facey-Thomas, Heidi; Halajian, Ali; Joshi, Lokesh; Ramjith, Jordache; Falcone, Franco H.; Horsnell, William; et al. (Journal of allergy and clinical immunology, 2022)
IgE to galactose alpha-1,3 galactose (alpha-gal) causes alpha-gal syndrome (delayed anaphylaxis after ingestion of mammalian meat). Development of sensitization has been attributed to tick bites; however, the possible role of other parasites has not been well studied. Our aims were to assess the presence, relative abundances, and site of localization of alpha-gal–containing proteins in common ectoparasites and endoparasites endemic in an area of high prevalence of alpha-gal syndrome, as well as to investigate the ability of ascaris antigens to elicit a reaction in a humanized rat basophil in vitro sensitization model. Levels of total IgE, Ascaris-specific IgE, and alpha-gal IgE were measured in sera from patients with challenge-proven alpha-gal syndrome and from controls without allergy. The presence, concentration, and localization of alpha-gal in parasites were assessed by ELISA, Western blotting, and immunohistochemistry. The ability of Ascaris lumbricoides antigen to elicit IgE-dependent reactivity was demonstrated by using the RS-ATL8 basophil reporter system. Alpha-gal IgE level correlated with A lumbricoides–specific IgE level. Alpha-gal protein at 70 to 130 kDa was detected in A lumbricoides at concentrations higher than those found in Rhipicephalus evertsi and Amblyomma hebraeum ticks. Immunohistochemistry was used to localize alpha-gal in tick salivary acini and the helminth gut. Non–alpha-gal–containing A lumbricoides antigens activated RS-ATL8 basophils primed with serum from subjects with alpha-gal syndrome. We demonstrated the presence, relative abundances, and site of localization of alpha-gal–containing proteins in parasites. The activation of RS-ATL8 IgE reporter cells primed with serum from subjects with alpha-gal syndrome on exposure to non–alpha-gal–containing A lumbricoides proteins indicates a possible role of exposure to A lumbricoides in alpha-gal sensitization and clinical reactivity.